Pengembangan LKPD Berbasis Model Problem Based Learning (PBL) Pada Mata Pelajaran Akuntansi Perusahaan Jasa dan Dagang Kelas XI SMK Negeri 4 Surabaya - Lidya Pratama Sari; Rochmawati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
Vocational education serves as a key factor in producing individuals with skills aligned to the needs of the workforce, one of which is implemented through Vocational High Schools (SMK). However, SMK graduates still dominate the open unemployment rate in Indonesia, indicating a mismatch between graduate competencies and industry demands. One of the contributing factors is the limited availability of Student Worksheets (LKPD) that support practicum activities, as well as the continued use of narrative-based questions that lack contextual relevance. The purpose of this study is to design and develop LKPD based on the Problem Based Learning (PBL) model for the topic of service and trading company accounting, which is expected to enhance students’ practical skills and make learning more relevant to industrial demands. The method used in this study is Research and Development (R&D). The ADDIE model was chosen because it offers a systematic, organized, and adaptable framework that facilitates the development of learning tools tailored to students’ needs while allowing continuous evaluation throughout the development process. Expert validation results show that the LKPD is considered highly feasible, with content feasibility at 88%, presentation at 96%, language at 88%, and media at 100%, resulting in an overall average score of 93%. Student responses to the LKPD were also highly positive, with a percentage of 99.5% categorized as Excellent. These findings indicate that the PBL-based LKPD effectively supports contextual and applicable accounting learning in vocational school.